Stakeholder relationship management [electronic resource] : a maturity model for organisational implementation - Bourne, Lynda (Gower ; Ashgat, 2009)
Providing the fundamental processes and practices for improving stakeholder management in endeavours such as projects, and program management offices (PMO), this work offers guidance on organisational survival during mergers and acquisitions, preparing for the tender bidding, and marketing campaigns.